Численное моделирование напряженно-деформированного состояния инновационных тонкостенных машиностроительных конструкций - Шейченко, Роман Игоревич; Ткачук, Николай Анатольевич; Бондаренко, Марина Александровна; Лунев, Евгений Александрович (НТУ "ХПИ", 2017)
В работе описаны результаты численного моделирования напряженно-деформированного состояния тонкостенных машиностроительных конструкций. На примере вагона-цистерны для перевозки жидкой серы исследовано влияние различных вариантов нагружения и конструктивных параметров на прочность элементов вагона. Обоснованы рекомендации по техническим решениям инновационного вагона-цистерны.

The paper describes results of numerical modeling of stress-strain state of thin-walled engineering structures. For example, for tank wagon for liquid sulfur transportation effect of different load modes and design parameters on strength of wagon components was studied. Recommendations for technical solutions of innovative tank-wagon were justified. According to results of multiple studies set of parameters, which is conformed to a complex of existing rules and criteria in terms of strength, is recommended. As a result of strength analysis the equivalent stresses for wagon structure are obtained. Evaluation of wagon structure conformity to normalized parameters of strength by I and III regimes was made by comparison of calculated stresses with the permissible values. Analysis of results led to conclusion that maximum equivalent stresses in all structural wagon elements don’t exceed the allowable ones for all load modes. This allows to conclude that wagon structure with recommended design solutions corresponds to the normalized strength parameters.
Numerical simulation of stress-strain state of thin-walled innovative engineering structures
Keywords: инновационное изделие; прочность; вагон-цистерна; жидкая сера; нагружение; innovative product; strength; tank-wagon